2022
DOI: 10.3390/biom12040539
|View full text |Cite
|
Sign up to set email alerts
|

Extraction of Phenolic Compounds from Populus Salicaceae Bark

Abstract: Lignocellulosic residues have the potential for obtaining high value-added products that could be better valorized if biorefinery strategies are adopted. The debarking of short-rotation crops yields important amounts of residues that are currently underexploited as low-grade fuel and could be a renewable source of phenolic compounds and other important phytochemicals. The isolation of these compounds can be carried out by different methods, but for attaining an integral valorization of barks, a preliminary ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 63 publications
0
12
0
Order By: Relevance
“…Previously, Egigu et al [ 45 ] reported that the extraction potential of solvents depend on their polarity strength. Several studies have proved the significance of high polar organic solvents for the improvement of extraction yield of phenolic compounds [ 46 48 ]. Highly hydroxylated aglycone forms of phenolic compounds are soluble in high polar solvents such as water and alcohols (ethanol and methanol) and hydroxy groups of phenolic compounds contribute to antioxidant activity [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, Egigu et al [ 45 ] reported that the extraction potential of solvents depend on their polarity strength. Several studies have proved the significance of high polar organic solvents for the improvement of extraction yield of phenolic compounds [ 46 48 ]. Highly hydroxylated aglycone forms of phenolic compounds are soluble in high polar solvents such as water and alcohols (ethanol and methanol) and hydroxy groups of phenolic compounds contribute to antioxidant activity [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previously, Egigu et al [45] reported that the extraction potential of solvents depend on their polarity strength. Several studies have proved the significance of high polar organic solvents for the improvement of extraction yield of phenolic compounds [46][47][48]. Highly hydroxylated aglycone…”
Section: Discussionmentioning
confidence: 99%
“…The extract was used to determine the content of total phenols and flavonoids. The total phenol content was determined by the Folin‐Ciocalteu method by microplate reader (Spectramax 190, USA) [31] . The total flavonoid content was determined by the aluminum nitrate colorimetric method [32] …”
Section: Methodsmentioning
confidence: 99%
“…The total phenol content was determined by the Folin-Ciocalteu method by microplate reader (Spectramax 190, USA). [31] The total flavonoid content was determined by the aluminum nitrate colorimetric method. [32] Total Polysaccharide Content Assay…”
Section: Total Phenolic and Total Flavonoid Content Assaymentioning
confidence: 99%
“…The choice of solvents in the present study was selected based on previous studies on their role in the extraction of polar compounds (Autor et al, 2022; Nawaz et al, 2020).…”
Section: Methodsmentioning
confidence: 99%